Religious Services or the Care of Souls in Reports on Clerics at the Moravian and Silesian Estates Belonging to the Prince of Liechtenstein from the Second Half of the Eighteenth Century - Pumpr, Pavel (Historical Studies on Central Europe, 2023)
The reform of the Catholic clergy initiated by the Council of Trent emphasized the importance of the practical exercise of the care of souls (cura animarum). The ideal priest should, following the example of Christ—the Good Shepherd, take responsible care of his ‘sheep’—the parishioners. The paper focuses on how the parish clergy performed pastoral care, based on the analysis of reports written on clerics working in the 1760s in ten Moravian and Silesian estates of the Prince of Liechtenstein. These reports prepared by the Prince’s officials mostly contain an evaluation of the performance of the pastoral care by the given cleric. They thus provide an interesting insight into the religious services offered by the lower clergy from the perspective of the owner of the estate, who was also the patron of the local parishes. They show that the Prince of Liechtenstein as the patron, together with his officials, supervised how the clerics provided for the spiritual needs of his subjects and furthermore through the exercise of the right of patronage he helped to provide his subjects with proper pastoral care.